2018
DOI: 10.1002/alr.22085
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use patterns in endoscopic sinus surgery: a survey of the American Rhinologic Society membership

Abstract: This study demonstrates the significant variation in perioperative antibiotic use among otolaryngologists. These results provide support for the establishment of evidence-based practice guidelines for perioperative antibiotic use in ESS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
(22 reference statements)
0
22
0
1
Order By: Relevance
“…The majority of otolaryngologists report prescribing prophylactic postoperative antibiotics for patients undergoing ESS for medically refractory CRS (from 62.3% 3 to 86.8% 15 ), most often citing a need to reduce the risk of postoperative infection (75.6%) 3 . Although this is a commonly held belief, there is a paucity of data concerning the incidence of postoperative sinus infections, which may range from 2.5% (2 of 79 in the present study) to 14.9% (30 of 202 in a previously reported study) 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of otolaryngologists report prescribing prophylactic postoperative antibiotics for patients undergoing ESS for medically refractory CRS (from 62.3% 3 to 86.8% 15 ), most often citing a need to reduce the risk of postoperative infection (75.6%) 3 . Although this is a commonly held belief, there is a paucity of data concerning the incidence of postoperative sinus infections, which may range from 2.5% (2 of 79 in the present study) to 14.9% (30 of 202 in a previously reported study) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review study on perioperative antibiotic use in otolaryngology concluded that the current evidence does not support the use of routine antibiotic prophylaxis for ESS 19 . Despite these findings, a great deal of variability exists in perioperative antibiotic practice patterns between surgeons performing ESS and across practice sites, 20 as post‐ESS antibiotic prescribing is generally still based on surgeon discretion 3,21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In unserer Recherche der neueren deutsch-und englischsprachigen Literatur fanden sich keine ähnlichen publizierten Umfragen im deutschsprachigen Raum. Internationale publizierte Umfragen beschränken sich meist auf das generelle Management, die prä-und postoperative medikamentöse Therapie bei Erkrankungen der Nasennebenhöhlen und die Durchführung ambulanter rhinologischer Eingriffe [11][12][13][14][15][16]. Sie wurden zum Teil bei Mitgliedern rhinologischer Gesellschaften durchgeführt, die eine entsprechende Spezialisierung aufweisen und zum Teil im ambulanten Sektor tätig sind.…”
Section: Diskussionunclassified
“…This is a topic of perennial importance as the drive toward thoughtful antibiotic stewardship continues across the medical field. Within our specialty, a recent survey of the American Rhinologic Society membership found that 59% of respondents “always” prescribe antibiotics after ESS 2 . Yet, despite the pervasiveness of this practice, a firm scientific basis has long been lacking.…”
mentioning
confidence: 99%